Kemampuan Pemahaman Konsep Siswa Berdasarkan Gender pada Pembelajaran Realistic Mathematics Education Berbantuan Alat Peraga PANDU - Utami, Citra; Anitra, Rien (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
The purpose of this study is to describe the ability to understand mathematical concepts based on gender after participating in Realistic Mathematics Education learning with the props, "Papan Pecahan dan Sudut" (PANDU). This research method was qualitative with quantitative descriptive research. The subjects in this study were fourth-grade elementary school students in Singkawang city. Data collection instruments were the researcher and the documentation of the results of the students' mathematical concept understanding ability tests. Data analysis techniques were scoring, assessment, categorization, description, and conclusion. The results showed; 1) the ability of male students to understand mathematical concepts after participating in RME learning with PANDU teaching aids had an average score of 80.35, which was in the high category; and 2) the ability of female students to understand mathematical concepts after participating in RME learning with PANDU teaching aids had an average of 78.52, which was in the high category. Based on the results of this study, it can be concluded that there is no difference in the ability to understand mathematical concepts between male students and female students after participating in RME learning assisted with PANDU teaching aids.